Study of effects of different stecklings planting and seed harvesting times on seed quantity and quality of Shirin cultivar of sugar beet - M.A. Chegini (Sugar Beet Seed Institute, 2014)
To determine proper radicle sowing and harvest date, an experiment was conducted in Ardabil Agricultural Research Station (Alarough) in 2003-04. Sugar beet variety Shirin was evaluated in split plot experiment based on randomized complete block design with four replications. The treatments consisted of four sowing dates including 5th March, 20th March, 4th April and 19th April in main plots, and four harvest dates including 15, 30, 45 and 60 days after 50% flowering stage in subplots. The maximum number of main stem (2.7 per plant), lateral stem (42.4 per plant) were recorded on second and first sowing dates. Plant height decreased from 128.03 cm in first planting to 106.5 cm in fourth planting. Plant dry weight on first, second, third, and fourth sowing dates was 389.6, 409.14, 344.9 and 300.9 g/plant, respectively. The highest seed yield and standard seed extraction coefficient was obtained in first planting date. Harvest date had significant effect on seed yield, seed size, and unfilled grain. Harvest at 45 days after flowering resulted in significant increase seed yield (2735.8 kg/ha) and 3.5-4.5 seed size percentage. Also, the highest rate of unfilled grain (%17.2) was obtained at first harvest date. It is recommended that to plant sugar beet radicle at first sowing date and seeds harvested 45 days after flowering.